Solving Performance Problems of the State Civil Apparatus (ASN) in Ramanuju District Cilegon City Seen from the Influence of Organizational Culture, Work Capability and Job Satisfaction - Ujang Suhardi; Dhany Isnaeni Darmawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research discusses how to resolve performance problems of the State Civil Apparatus (ASN) in Ramanuju Village, Cilegon City, seen from the influence of organizational culture, work ability and satisfaction. The population and sample in this study were 91 respondents in Ramanuju Village, Cilegon City, sampling using the saturated sampling method. Data was collected using a questionnaire method, and the analysis used was data instrument testing, classical assumption testing, multiple regression analysis, coefficient of determination and hypothesis testing using SPSS for Windows. Based on the research results, it can be concluded that: the first hypothesis test shows that there is a partial significant influence of the organizational culture variable on the performance of the State Civil Apparatus (ASN) t-count 4.903 > t-table 1.986, the second hypothesis shows that there is a partial significant influence of the variable work ability on the performance of the State Civil Apparatus (ASN) t-count 2.048 > t-table 1.986, the third hypothesis shows that there is a partially significant influence of the job satisfaction variable on the performance of the State Civil Apparatus (ASN) t-count 2.830 > t-table 1.986 and the fourth hypothesis shows that there is a significant simultaneous influence of the variables organizational culture, work ability and job satisfaction on the performance of the State Civil Apparatus (ASN) f-count 19.741> f-table 3.10. The limitations of this research are that for further research, it is hoped that the research methodology and other variables will be changed so that it is hoped that there will be improvements or strengthening of performance